QOLP-10. MONITORING TRENDS IN PATIENT DISTRESS IN GLIOBLASTOMA USING THE PHQ4 QUESTIONNAIRE. (9th November 2020) - Huan Vo, Anh; Hambelton, Connor; Popp, Lauren; Dew, Verda; Turchan, Maria; Gallamore, Sofia; Fu, Rochelle; Neuwelt, Edward; Ambady, Prakash
Abstract: OBJECTIVE: To identify the trend of distress over time and whether palliative care (PC) referral and visit affected distress level in glioblastoma (GBM) patients. BACKGROUND: GBM patients experience significant distress due to their prognosis and neurologic involvement. All subjects in the neuro-oncology clinic at our institution routinely receive the Patient Health Questionnaire-4 (PHQ4) which is a validated screening tool that comprises a section for generalized anxiety disorder (GAD2) and a depression screen (PHQ2). DESIGN: This prospective study was approved by the institutional review board. GBM patients who started radiation therapy on 1/1/2019 or later were included. Patients with a GAD2 or PHQ2 of 3 or above were categorized as present for anxiety or depression. A logistic mixed-effects model was used to test the trend of anxiety or depression over time and the impact of PC referral and visit. RESULT: 131 PHQ4 questionnaires from 39 newly diagnosed GBM patients (mean age: 59.9yrs ± 15.0; 23M/16F) at the pre-radiation, post radiation and at least every 2 months thereafter were reviewed. Before radiation, 54.8% of patients reported anxiety, higher than at 1-month post radiation (23.5%), 2-3 months (41.4%), 4-6 months (20.0%), and after 6 months (25.0%). This temporal trend is significant ( P = 0.0385) after adjusting for patient characteristics such as age, gender and performance status. The proportions of anxiety were not different among visits without PC referral (23.7%), with PC referral and no PC visit (42.4%), and with PC visit (32.4%, P = 0.64). We did not identify a similar temporal trend in depression. CONCLUSION: Our data suggests that anxiety is more prevalent than depression in this cohort. This study identifies subjects to be at a greatest likelihood of experiencing anxiety at the pre-radiation time point. Focused interventions at this time point may help improve the patient's overall quality of life.